Use of a large Stokes-shift fluorophore to increase the multiplexing capacity of a point-of-care DNA diagnostic device. - Richardson, J; Morgan, T; Andreou, M; Brown, T (2013)
The intense demand for fluorescence-based point of care (POC) DNA diagnostics is driving developments to reduce the size of instrumentation, imposing limitations on the optical hardware that can be included. Here we describe a combination of instrumentation and fluorogenic probes to detect three fluorophores using two excitation and two detection channels.